The linguoaxiological aspect: the current characteristics of parental linguistic behavior - Abdykhanova Б.А.; Akkaliyeva А.Ф.; Meirambekova Л.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article explores how language manifests concepts of values, which adapt and transform in accordance with the socio-cultural context, and the changes they undergo in the current globalized environment. The importance of studying the issue of parental linguistic behavior is approached as a key topic. To determine and assess the contemporary nature of this issue, the article examines fundamental aspects of axiology, including the relationship between language and cultural values. It also analyzes the role of linguistic units as indicators of parents’ worldviews and their influence on shaping relationships with children. Educational models historically employed in raising children within the Kazakh nation are presented through examples from literary works. These models are necessary for conducting a comparative analysis and evaluation of traditional and modern methods of upbringing. Examples of motivational practices previously used in child-rearing are proposed. The associative analysis results presented in the article serve as linguistic cues for parents. Examples drawn from social media highlight contemporary shifts in youth perspectives and attitudes. Furthermore, the survey’s linguistic data can be used as proof that social issues have a significant impact on how parents raise their children, how families interact, and how children develop their values.